Phytopathology Research - Peng, You-Liang.; Liu, Jun.; Zhou, Xueping; SpringerLink (Online service) (London : BioMed Central : Imprint: BioMed Central.)
Phytopathology Research is an open access journal dedicated to advancing our understanding of plant diseases and developing effective environment-friendly measures for disease control. The journal publishes fundamental and applied research on broad aspects of plant diseases. These include but are not limited to genetics and molecular biology of plant disease resistance or susceptibility, molecular analysis of relevant traits in agriculturally important phytopathogens, the ecology of pathogens and plant-associated beneficial micro-organisms, disease etiology, epidemiology and disease management, and technical innovations that advance the phytopathology research. Articles are selected based on novelty, importance, scientific validity, and interest to the readers.
Keywords: Botany; Plant diseases; Plant Science; Plant Pathology